2017
DOI: 10.1097/aci.0000000000000388
|View full text |Cite
|
Sign up to set email alerts
|

Climate changes and Hymenoptera venom allergy: are there some connections?

Abstract: Distribution and consistency of allergenic species including venomous insects are interested by accelerated dynamics caused by climate changes and globalization. Owing to the expansion of ranges of native species and colonization of invasive ones, even in the uncertainty of present available models, new challenges presented by stinging Hymenoptera should be expected in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Climate change, habitat destruction and accidental introduction of invasive species are drastically changing the distribution of some clinically relevant insects among different geographical regions [48]. In Europe, P. dominula has expanded its habitat toward Central and Northern Europe [49].…”
Section: Potential Novel Elicitors Of Hymenoptera Venom Allergy In Eumentioning
confidence: 99%
“…Climate change, habitat destruction and accidental introduction of invasive species are drastically changing the distribution of some clinically relevant insects among different geographical regions [48]. In Europe, P. dominula has expanded its habitat toward Central and Northern Europe [49].…”
Section: Potential Novel Elicitors Of Hymenoptera Venom Allergy In Eumentioning
confidence: 99%
“…Furthermore, Münstedt et al ( 19 ), reported the occurrence of more severe non-allergic reactions to bee venom during the spring months when compared to later periods. It is also important to consider the impact of climate change, as the available data support the presence of positive correlations between climate change and HVA ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Finland (~5,5 million habitants), there is fewer than one death per year caused by wasp sting (Hirvonen and Jäntti 1995), whereas in neighboring Sweden (over 10 million habitants), there have been two deaths annually (Johansson et al 1991). The situation may change, however, with increasing human-wasp encounters due to wasp distribution shifts with climate change (Sumner 2022;Turillazzi and Turillazzi 2017). According to Smallheer (2013), 0.05 to 5% of the human population has hypersensitivity to Hymenoptera venom (bees, wasps, and hornets).…”
Section: The Unloved Waspmentioning
confidence: 99%
“…Urbanization affects wasp populations in several ways: urbanization destroys and fragments habitats but also provides novel biotopes with the potential to provide shelter, nest sites, and food (McDonald et al 2013;Turillazzi and Turillazzi 2017). The changing environment may increase human-wasp encounters, further highlighting the need to develop strategies for living well together.…”
Section: Environmental Changes and Increasing Human-wasp Encountersmentioning
confidence: 99%